Look out, secret seven - Blyton, Enid (Hodder Children's London, 2002)
An enduringly popular series, now with fun new covers! What would the Seven do without Scamper the spaniel? First he discovers an unwanted visitor - then he protects the Seven as they spy on a thief late at night in the woods ...